An Unusual Complication of PEG Feeding After Pancreatico-Gastrostomy - Phillips, Mary Elizabeth; Hosie, Katy; Griffiths, Edward J; Low, Nadeen; Gallagher, Michelle C; Tibbs, Christopher J; Karanjia, Nariman D (JOP. Journal of the Pancreas, 2014)
Context We describe a late complication of the pancreatico-gastrostomy (PG) anastomosis following pancreatico-duodenectomy (PD). Case report A percutaneous endoscopic gastrostomy (PEG) feeding tube was inserted many months post-operatively. In this patient activated pancreatic enzymes eroded the gastrostomy tract, resulting in pain, recurrent infection and eventual removal of the gastrostomy tube. Conclusions Where surgical insertion of a feeding jejunostomy is not viable or deemed too high risk after Whipple or PPPD, we recommend careful consideration of PEG tube insertion in patients with PG reconstruction. If a PEG is used the prophylactic use of Lanreotide is recommended. Image: CT scan following PEG-J insertion.